2023
DOI: 10.3171/2022.5.jns212846
|View full text |Cite
|
Sign up to set email alerts
|

Early outcomes of the American Academy of Neurological Surgery Emerging Investigator Program in promoting neurosurgeon-scientists

Abstract: eurosurgeoNs have made important contributions to the science and practice of medicine. [1][2][3][4][5][6][7] The research efforts of neurosurgeon-scientists have generated paradigm-shifting advancements that have changed clinical practice. After neurosurgical training was standardized to 7 years in 2013, residency programs adopted training curricula to include dedicated electives that could be used for research endeavors and help neurosurgeon-scientists launch academic careers. Nevertheless, there has been a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…For example, the Society of Vascular Surgery Foundation Career Development Award has provided supplemental funds to 31 K08-awarded and 10 K23-awarded vascular surgeons since 1999, 62% of whom were successful in transitioning to independent funding (R series award) . Furthermore, an early analysis of the American Academy of Neurological Surgery Emerging Investigator Program found that providing a structured mechanism for mentoring young surgeon-scientists resulted in 67% of the recipients successfully earning NIH funding . It was concluded by Keswani et al that surgeons successful in transitioning from a mentored to independent career did so in the first 9 years after fellowship.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Society of Vascular Surgery Foundation Career Development Award has provided supplemental funds to 31 K08-awarded and 10 K23-awarded vascular surgeons since 1999, 62% of whom were successful in transitioning to independent funding (R series award) . Furthermore, an early analysis of the American Academy of Neurological Surgery Emerging Investigator Program found that providing a structured mechanism for mentoring young surgeon-scientists resulted in 67% of the recipients successfully earning NIH funding . It was concluded by Keswani et al that surgeons successful in transitioning from a mentored to independent career did so in the first 9 years after fellowship.…”
Section: Discussionmentioning
confidence: 99%
“…The success of the Academy EIP is evident; of the 15 scholars who were part of the first 2 cohorts of the EIP, 10 (67%) have secured NIH funding. 12 As a well-designed intervention at a critical moment when junior faculty may not otherwise progress to NIH funding, this limited program is a model that can be easily adapted on a local level to support junior neurosurgeon-scientists as grants are being revised and resubmitted. Expansion on these initial successes is ongoing; for example, the American Association of Neurological Surgeons/Congress of Neurological Surgeons Spine Section is launching a spine-focused EIP, and the SNS-backed Neurosurgeon-Scientist Training Program looks to serve as a formal, funded, mentored research program for neurosurgery residents.…”
Section: Successful Transition To Independent Neurosurgeon-scientistmentioning
confidence: 99%
“…The current neurosurgery training approach has incorporated many of these features into their integrated training model with great success. [23][24][25] Finally, parts of the research training paradigm can be incorporated into residency and fellowship for all trainees, with only those seeking a surgeon-scientist career spending 18 to 36 months dedicated to research. It will take time to evolve from the current model so it is also crucial to consider ways to presently mitigate these common pain points, including establishing a research track that can fit within the existing ACGME curriculum and awarding catalyst grants to productive residents that enable them to return to clinical work but allow the research to continue in the mentor's laboratory with a supporting technician or research staff scientists.…”
Section: Redesign the Surgeon-scientist Training Paradigmmentioning
confidence: 99%
“…However, the concepts of early engagement, continuity, and full integration of research within the surgical training years, as well as early specialization should guide the redesign of surgical training paradigms. The current neurosurgery training approach has incorporated many of these features into their integrated training model with great success 23–25 . Finally, parts of the research training paradigm can be incorporated into residency and fellowship for all trainees, with only those seeking a surgeon-scientist career spending 18 to 36 months dedicated to research.…”
Section: Blueprint To Sustain and Grow The Impact Of Surgical Scientistsmentioning
confidence: 99%